Association of Health Service Quality with Patient Satisfaction in Primary Healthcare Center of Gedongtengen Yogyakarta - Mustika, Yoan Ajeng; Nugrahaningtyas Wahjuning Utami, Jacoba; Sukismanto, Sukismanto (Journal of Health Education, 2019)
Background: Quality of service is an important indicator in measuring patient satisfaction. Based on the results of a preliminary study in 10 patients, in terms of the dimension of reliability quality, 30% said satisfied and 70% less satisfied; in terms of the dimension of empathy quality, 20% said very satisfied and 80% satisfied; in terms of the dimension of assurance, 90% said satisfied and 10% unsatisfied; in terms of the dimension of responsiveness, 10% said very satisfied, 80% satisfied and 10% less satisfied; in terms of the dimension of tangible, 90% said satisfied and 10% less satisfied. the aim of this study is to identify the association between dimension of health service quality and patient satisfaction in Maternal & Child Health and Family Planning Polyclinic at Pimary Healthcare Center (PHC) of Gedongtengen, Yogyakarta. Methods: This research employed a descriptive analytical method with cross sectional approach. The population consisted of 170 respondents. Samples were taken using purposive sampling, resulting in 119 respondents as samples. Data were statistically tested using Kendall’s Tau. Results: The results of statistical test indicated that there was a correlation between the dimension of reliability, empathy, assurance, responsiveness, and tangible to patient satisfaction. Conclusion: There are correlations of the dimensions of reliability, empathy, assurance, responsiveness and tangible with patient satisfaction.